The activity theory in mathematics interactive digital didatic material - de Souza Chiari, Aparecida Santana [UNESP]; de Carvalho Borba, Marcelo [UNESP]; Souto, Daise Lago Pereira [UNESP] (FapUNIFESP (SciELO), 2019)
In this article, we discuss how the formal mathematical language, digital technologies, the internet, virtual learning environments, and the interaction between distance learning participants can influence and transform the production of knowledge in distance learning courses. We consider the research that gave rise to this article as a collective case study, since the data were produced during the development of Linear Algebra disciplines of four distance teacher education courses in Mathematics linked to the Open University of Brazil (UAB). We base our analyzes on the theory of activity and the epistemological view that surrounds the construct humans-with-media. Methodologically, we adopt the qualitative paradigm, having as sources of data production observation in virtual learning environments, interviews, political pedagogical projects and field notes. Data analysis was based on the grounded theory rooted in the activity theory itself. The results indicated that the difficulty in communicating and expressing the formal mathematical language in the virtual learning environment generated tensions and transformations that resulted in the production of interactive digital didactic material.
A Teoria da Atividade na Produção de Material Didático Digital Interativo de Matemática
Keywords: Digital Technologies; Distance Education; Grounded Theory; IDDM; Linear Algebra